How Well is the Implementation of CAPM in Condition of Market Anomaly? Case in Market Overreaction Anomaly at Indonesia Stock Exchange - Ferikawita M. Sembiring (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This study aims to test the occured of the market anomaly, iemarket overreactions in Indonesian stock market at the Covid-19 pandemic. If the event occurs then be tested whether a contrarian investment strategy is relevant to be implemented. It will also be tested whether the CAPM's market risk factor will affect the returns. The data from the Indonesia Stock Exchange (IDX) used are the stock price in periods of January 2019-December 2020, which during the pandemic were have the potential to be profitable or detrimental. Through the formation of the portfolios that called as as the winner and the losers, testing of returns reversals could be done to prove the occurs of the market overreaction. The results of this research are as follows: First, markets overreaction anomaly event has occured in Indonesian stock market in periods of Covid-19 pandemic. The reversal of return occurs for most shares those have the potential to be profitable or detrimental, or have been proven those it profits rates has increased or decreased in the periods of the pandemic. Second, the contrarian strategy is relevant to be implemented in the short term in Indonesian stock market, which is in this pandemic. By implementing the contrarian strategy, a profitable return is obtained from the difference between the returns of the losers and the winners through their each of observation period. Third, market risk factors based on the CAPM have a significant effect only for the losers stocks.